Prominent Signet Ring Cell Morphology in a Pulmonary Squamous Cell Carcinoma - Nuri YİĞİT; Ertuğrul ÇELİK; İbrahim YAVAN (Federation of Turkish Pathology Societies, 2018)
In daily practice, signet ring cell morphology immediately brings to the mind the possibility of an adenocarcinoma at first glance. The signet ring cell appearance has been described and is well-known in a wide variety of some other neoplasms as well. Surprisingly however, neoplastic cells having the same morphology can unexpectedly be encountered in not previously well-documented tumors. Here, we present an 85-year-old man diagnosed with primary pulmonary squamous cell carcinoma and a large signet ring cell population. Examination of the lobectomy specimen and further radiological workup was consistent with stage I disease. Signet ring cell variant of squamous cell carcinoma is a very infrequent tumor and has been reported in only eight cases from skin, cervical and oral cavity biopsies as well as in one case of pulmonary acantholytic variant of squamous cell carcinoma with focal signet ring cells. To be aware of this entity is crucial for pathologists to reach the correct diagnosis, particularly in cytological samples, because of its potentially modifying effect on treatment options and patient management compared to adenocarcinomas. Our patient remained in clinical remission during the 9-month follow-up.